The description of husband's support in breastfeeding for primiparous mothers - Nakhlah, Fidela; Agrina, Agrina; Zulfitri, Reni (Journal of Midwifery and Nursing, 2025)
Breast milk is the best source of nutrition for infants and provides long-term health benefits for both the mother and the baby. The success of breastfeeding is influenced by various factors, one of which is the support of the husband. This support can take the form of emotional, informational, physical, and evaluative support. This study aims to describe the husband's support in breastfeeding among primiparous mothers. Methods: This study used a descriptive statistical design with 88 respondents selected through purposive sampling. The instrument used was a questionnaire developed by Ratu (2019). Data analysis was performed using univariate analysis in the form of frequency distribution tables and percentages. Results: The majority of respondents were aged 25-30 years (58%), had a high school education (42%), and worked as private sector employees (39.8%). Most of the respondents had infants aged 8 months (26.1%), and the duration of breastfeeding was in accordance with the infant's age. The husband's support for breastfeeding mothers was categorized as good, with informational support reaching 60.2%, emotional support 48.9%, physical support 47.7%, and evaluative support 52.3%. Conclusion: Informational support was the most commonly provided form of support by husbands. Future research is recommended to use a qualitative approach to explore husbands' support in breastfeeding in more depth.